Phytoremediation of a Petroleum‐Hydrocarbon Contaminated Shallow Aquifer in Elizabeth City, North Carolina, USA. Issue 2 (March 2014) - Nichols, Elizabeth Guthrie; Cook, Rachel L.; Landmeyer, James E.; Atkinson, Brad; Malone, Donald R.; Shaw, George; Woods, Leilani
<x xml:space="preserve">Abstract</x> A former bulk fuel terminal in North Carolina is a groundwater phytoremediation demonstration site where 3, 250 hybrid poplars, willows, and pine trees were planted from 2006 to 2008 over approximately 579, 000 L of residual gasoline, diesel, and jet fuel. Since 2011, the groundwater altitude is lower in the area with trees than outside the planted area. Soil‐gas analyses showed a 95 percent mass loss for total petroleum hydrocarbons (TPH) and a 99 percent mass loss for benzene, toluene, ethylbenzene, and xylenes (BTEX). BTEX and methyl tert‐butyl ether concentrations have decreased in groundwater. Interpolations of free‐phase, fuel product gauging data show reduced thicknesses across the site and pooling of fuel product where poplar biomass is greatest. Isolated clusters of tree mortalities have persisted in areas with high TPH and BTEX mass. Toxicity assays showed impaired water use for willows and poplars exposed to the site's fuel product, but Populus survival was higher than the willows or pines on‐site, even in a noncontaminated control area. All four Populus clones survived well at the site. © 2014 Wiley Periodicals, Inc.*